DISTRIBUTION ANALYSIS OF DOCTORS IN INDONESIA - Agung Dwi Laksono; Ilham Akhsanu Ridlo; Ernawaty Ernawaty (Indonesian Journal of Health Administration, 2020)
Background: The distribution of health workers in Indonesia raises an interesting discussion since Indonesia as an archipelagic country has a wide geography and challenges for fulfilling equitable health services.Aim: This study identified factors related to the distribution of doctors in provinces of Indonesia.Methods: Advanced analysis of secondary data was done and obtained from the "Data and Information: Indonesian Health Profile in 2017". The units analyzed in this study were all 34 provinces in Indonesia. The variables analysed were the number of doctors, population, density, percentage of poor population, the number of hospitals, and the number of primary healthcare centers.Results: Variability in the number of doctors was very wide. The more the population is, the more attractive it is for doctors to conduct practices in the provinces. The denser the population are, the more doctors are interested to work in the provinces. It also figured out that doctors tend to opt to work in the provinces which have more hospitals and primary healthcare centers.Conclusions: Out of five independent variables studied, there were four variables related to the number of doctors distributed in the provinces. Population, density, the number of hospitals, and the number of primary healthcare centers were positively related to the number of doctors. The results of this study were important for doctor redistribution policy in Indonesia. Keywords: distribution analysis, doctor distribution, health resources management, health workers.